2008
DOI: 10.1002/jor.20584
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of mesenchymal stem cells in a canine disc degeneration model

Abstract: Transplantation of mesenchymal stem cells (MSCs) is effective in decelerating disc degeneration in small animals; much remains unknown about this new therapy in larger animals or humans. Fas-ligand (FasL), which is only found in tissues with isolated immune privilege, is expressed in IVDs, particularly in the nucleus pulposus (NP). Maintaining the FasL level is important for IVD function. This study evaluated whether MSC transplantation has an effect on the suppression of disc degeneration and preservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 51 publications
(50 reference statements)
2
172
0
1
Order By: Relevance
“…Nevertheless there are now both animal and human studies into cell therapies for the disc, suggesting that this approach may be feasible. It has been shown that reinsertion of autologous nucleus pulposus cells or stem cells delays degeneration in experimental models of disc degeneration [32,39,65,80,98,108] and injection of autologous nucleus pulposus cells are being used in humans with herniated discs [65]. However, it is not yet clear what the optimal implant will be.…”
Section: Tissue Engineering and The Intervertebral Discmentioning
confidence: 99%
“…Nevertheless there are now both animal and human studies into cell therapies for the disc, suggesting that this approach may be feasible. It has been shown that reinsertion of autologous nucleus pulposus cells or stem cells delays degeneration in experimental models of disc degeneration [32,39,65,80,98,108] and injection of autologous nucleus pulposus cells are being used in humans with herniated discs [65]. However, it is not yet clear what the optimal implant will be.…”
Section: Tissue Engineering and The Intervertebral Discmentioning
confidence: 99%
“…MSCs have also been widely used for treatment of osteoarthritis in dogs, a progressive degenerative condition that also has an associated inflammatory component. Studies of canine adiposederived MSC (Ad-MSC) and bone marrow-derived MSC (BM-MSC) injected into the elbow and hip joints of dogs with osteoarthritis produced positive results in terms of improvement in clinical measures of osteoarthritis reported in most investigations [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple preclinical animal studies have demonstrated the efficacy of intradiscally injected mesenchymal stem cells (MSCs) to induce disc regeneration. 1,2,16,18,20,21,25,[31][32][33][34]38,39,49,53,56,60,[64][65][66]69,73,83,87,90 Allogeneic mesenchymal progenitor cells (MPCs) are the earliest uncommitted clonogenic population of bone marrow stromal cells and have also successfully repaired the extracellular matrix following their injection into degenerative ovine discs. 25 Moreover, when ovine MPCs combined with the chondrogenic agent pentosan polysulfate (PPS) were embedded in a gelatin sponge and placed in a biodegradable cage that was implanted into the interbody space of ovine cervical spines, the cage became filled with a predominately cartilaginous matrix.…”
mentioning
confidence: 99%